Enhancing the finance function in line ministries - Kraan, Dirk-Jan (OECD Publishing, 2017)
Despite fulfilling a crucial role in the delivery of public services, the finance function of line ministries has received little attention both in the past and in the present. This paper will focus on the finance function in line ministries, explain why a strong finance function is of paramount importance in the current era of lean and compact government and identify the reforms that need to be implemented in order to make this possible